Developing policy recommendations for controlling energy drink consumption in secondary school students using social marketing theory, Shiraz, Iran: A study protocol - Mohammadhassan Rostami; Mina Babashahi; Masoud Karimi; Soheila Khodakarim (PLoS ONE, 2025)
Background Energy drink (ED) consumption has risen sharply among children and adolescents, posing health risks such as obesity and overweight, heart problems, mood disorders, and insomnia. Recognizing these concerns, international organizations have issued guidelines discouraging adolescent ED consumption, leading to policy measures in many countries. This study leverages social marketing theory to develop targeted policy recommendations for managing ED consumption in secondary school students. Methods This study utilizes a cross-sectional design with a mixed-methods approach to collect data and formulate policy recommendations. A multistage cluster sampling method was employed to randomly select students from 24 schools, serving as the primary data source. Information is gathered through a questionnaire based on the Theory of Planned Behavior (TPB). Additionally, a food environment analysis of the selected schools, a critical factor influencing ED consumption, is conducted using the NEMS-S INFORMAS tool. This tool assesses the availability, pricing, and marketing of EDs. The study further explores stakeholder perspectives through key informant interviews and a systematic literature review, providing valuable insights into existing policy frameworks. The study aims to develop actionable policy recommendations to effectively address ED consumption by synthesizing findings from all these phases. Discussion The social marketing model focuses on understanding the audience and evaluating outcomes to develop effective policy proposals. It is particularly useful for behavior change policies, offering evidence-based recommendations that often surpass traditional health promotion methods. This study will analyze ED consumption and its influencing factors using the model’s constructs to present informed and practical policy recommendations.